Ulama and Manuscripts in Minangkabau: Safeguarding the Intellectual Heritage of Sheikh Abdul Laṭīf Shakūr - Shofiyanti, Lilis (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
The Wikisource Loves Manuscripts (WILMA) program, which was implemented in 2023, was successful in preserving manuscript collections in West Sumatra, particularly in Balaigurah, in the Agam Regency. This digitalization effort includes preserving the manuscripts at their current location, Bunayya Kindergarten. One of the collections preserved under this program is the manuscript collection of Sheikh Abdul Laṭīf Shakūr, which is both culturally and historically important.